Virology, serology, and demography of hepatitis E viremic blood donors in South East England. Issue 6 (3rd February 2016) - Tedder, Richard S.; Tettmar, Kate I.; Brailsford, Su R.; Said, Bengu; Ushiro‐Lumb, Ines; Kitchen, Alan; Morgan, Dilys; Lattimore, Sam; Tossell, Joanne; Ijaz, Samreen; Hewitt, Patricia E.
Abstract : BACKGROUND: Hepatitis E virus (HEV) Genotype 3 (G3) in England comprises two principal phylogenetic groups (Group 1 and Group 2) and can be transmitted by transfusion. Unselected screening identified 79 viremic donors; 76 participated in a follow‐up study. STUDY DESIGN AND METHODS: Viral RNA dynamics, phylogenetics, and seroconversion were characterized in the donors. Detailed demographic, travel, clinical, and lifestyle questionnaires were undertaken. RESULTS: The majority of viremic individuals (57/79) were seronegative at time of donation but all seroconverted. Viremia was short‐lived, with a median of 6.5 weeks to confirmed viral clearance. All infections were acquired in the United Kingdom and were G3, with Group 2 viruses predominating (43/54; 80%). Infection was associated with some clinical symptoms both at and after donation (8/77; 10%). Viral loads and symptoms were more pronounced in Group 1 infections. There was no serologic evidence of reinfection. Donors were more commonly male (p = 0.002); both male and female donors were older than comparator donors. Animal contact was unlikely to be the source of infection. Consumption of chicken and pig meat was common to all infected donors; processed pig meat was most commonly purchased from one particular retail chain. CONCLUSION: Viremic donors represent primary infection in older members of the community and reflect a widespread zoonotic in the United Kingdom. The two phylogenetic groups of HEV G3 display different pathogenicity and the more common Group 2 appears less adapted to humans. There are no objective demographic criteria that can identify donors at enhanced HEV risk.